Surface sediment and phytoplankton diatoms across a trophic gradient in tropical reservoirs: new records for Brazil and São Paulo State - Bartozek, Elaine Cristina Rodrigues [UNESP]; Zorzal-almeida, Stéfano; Bicudo, Denise C. (Instituto de Botânica, 2018)
This, study aimed to inventory the diatom flora of tropical reservoirs from southeastern region of Brazil under oligo- to hypereutrophic conditions. We collected diatom samples from the surface sediment and phytoplankton (summer and winter) in 41 sites (ten reservoirs). Seventy-eight taxa, distributed in 28 genera, were identified in the surface sediment and phytoplankton samples. Nizschia was the most representative genus, with nine species. Six taxa represent new records for Brazil and six for São Paulo State; ten taxa were identified at the genus level and probably represent new species. Additionally, this study contributed with data on the ecology of the species and evidenced the necessity of floristic surveys to improve the knowledge about tropical diatom biodiversity.

Este estudo visou inventariar a flora diatomológica de represas tropicais em condições oligo- a hipereutróficas da região sudeste do Brasil. As amostras abrangeram diatomáceas do sedimento superficial e fitoplâncton (verão e inverno) em 41 locais (dez represas). Setenta e oito táxons, distribuídos em 28 gêneros, foram identificados nas amostras de sedimento superficial e fitoplanctônicas. Nitzschia foi o gênero mais representativo, com um total de nove espécies. Seis táxons representam novas citações para o Brasil e seis para o Estado de São Paulo; dez táxons foram identificados em nível de gênero e provavelmente representam novas espécies. Adicionalmente, este estudo contribuiu com informações sobre a ecologia dessas espécies e permite enfatizar a necessidade de estudos florísticos para ampliar o conhecimento da biodiversidade de diatomáceas tropicais.
Diatomáceas de sedimentos superficiais e fitoplanctônicas ao longo de um gradiente trófico em reservatórios tropicais: novos registros para o Brasil e Estado de São Paulo
Keywords: biodiversity; diatom flora; ecology; biodiversidade; ecologia; flora diatomológica